An Assessment of Human-Wildlife Conflict in Basanta Corridor: a Case Study from Kailari Rural Municipality, Nepal - Hem Chandra Joshi; Prakash Ojha; Shiva Khadka; Sirjana Adhikari (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
The human-wildlife conflict (HWC) has always been a subject of concern for conservationists and people living in the proximity of forests. Nepal has witnessed increasing incidents of HWC at an alarming rate in the last few years. The study was carried out to understand the causes and trends of HWC in Kailari Rural Municipality and the perception of people towards wildlife conservation. The major tools used for the data collection were key informant interviews and questionnaire surveys. The data collected from the field was analyzed using descriptive and inferential statistics. This study showed that crop plundering, human injuries & death, livestock injuries, and killing by wildlife was the common form of HWC and the animals with high incidents of conflict were a monkey, wild boar, elephant, tiger, blue bull, deer, and rabbit in recent years. The main crops damaged in the area were wheat, paddy, maize, peanuts, mustard, etc. The problematic animals were found to be monkeys, rabbits, and wild boars. The study concluded that tigers and elephants attack were the major problems in the areas near Dudhwa National Park (India). None of the respondents have got compensation for the loss of crops, livestock, and even in case of human casualties. Most of the respondents believed that animals come to the cropland due to farmland nearer to forest areas and lack of food for the animals.